Nordcan.R: a new tool for federated analysis and quality assurance of cancer registry data - Larønningen, Siri; Skog, Anna; Engholm, Gerda; Ferlay, Jacques; Johannesen, Tom Børge; Kristiansen, Marnar Fríðheim; Knoors, Daan; Kønig, Simon Mathis; Olafsdottir, Elinborg J.; Pejicic, Sasha; Pettersson, David; Skovlund, Charlotte Wessel; et al. (Frontiers in Oncology, 2023)
Aim of the article We present our new GDPR-compliant federated analysis programme (nordcan.R), how it is used to compute statistics for the Nordic cancer statistics web platform NORDCAN, and demonstrate that it works also with non-Nordic data. Materials and methods We chose R and Stata programming languages for writing nordcan.R. Additionally, the internationally used CRG Tools programme by International Agency for Research on Cancer (IARC/WHO) was employed. A formal assessment of (GDPR-compliant) anonymity of all nordcan.R outputs was performed. In order to demonstrate that nordcan.R also works with non-Nordic data, we used data from the Netherlands Cancer Registry. Results nordcan.R, publicly available on Github, takes as input cancer and general population data and produces tables of statistics. Each NORDCAN participant runs nordcan.R locally and delivers its results to IARC for publication. According to our anonymity assessment the data can be shared with international organizations, including IARC. nordcan.R incidence results on Norwegian and Dutch data are highly similar to those produced by two other independent methods. Conclusion nordcan.R produces accurate cancer statistics where all personal and sensitive data are kept within each cancer registry. In the age of strict data protection policies, we have shown that international collaboration in cancer registry research and statistics reporting is achievable with the federated analysis approach. Undertakings similar to NORDCAN should consider using nordcan.R.